Birch (Betula pendula Roth.) responses to high UV-B radiation - Wulff, A.; Anttonen, S.; Pellinen, R.; Savonen, E.-M.; Sutinen, M.-L.; Heller, W.; Sandermann, H. Jr.; Kangasjärvi, J. (Boreal Environment Research Publishing Board, 2024)
Responses of European silver birch seedlings to highly enhanced levels of UV-B radiation (14.4 or 22.5 kJ m–2 d–1 UV-BBE) were studied in a glasshouse experiment. Visible symptoms, membrane lipid composition, secondary metabolites, mRNA levels of chalcone synthase (Chs), localisation of Chs mRNA and leaf structure were analysed. Interveinal chlorosis and asymmetric leaves were induced by UV-B. A significant UV-B -induced increase in 18:2 fatty acid of both glycolipids and phospholipids was detected. UV-B dependent increase in accumulation of a quercetin-3-glycoside and three other compounds, as well as a transient increase in Chs mRNA levels are indicative of induced biosynthesis of flavonoids. In situ experiments showed that mRNA of Chs was mainly found in the upper mesophyll and vascular bundle tissues. Structural observations showed injuries caused by high irradiances. At the light microscopy level there was first a reduction in palisade parenchyma and later a more dense structure of spongy parenchyma cells. Electron microscopy demonstrated an increase in vacuolar membrane whorls and dark bodies, occurrence of lipid material and darkened chloroplast stroma in mesophyll cells. However, results also indicated that Betula pendula is capable of inducing defence reactions such as biosynthesis of flavonoids even at very high UV-B radiation.